Adverse drug reactions resulting from COVID-19 treatment in university members - Mendoza Gutierrez , Lizzy Jeanette (2023)
Objective: To analyze the extent to which members of the community of a private university report the presentation of adverse drug reactions related to COVID-19 pharmacotherapy. Material and Methods: Quantitative approach, cross-sectional descriptive type, non-experimental design, the sample was 159 members of the university community, stratified probabilistic sampling, the technique was a virtual survey, the instrument was a questionnaire made with Google Forms; the results were expressed as mean, standard deviation, percentage frequency, and for the statistical analysis the following tests were used: chi square and 95% confidence interval with a significance level 0.05. Results: most of the participants were female (63.32%), married (59.12%) and with a mean age of 44.46 years; most of them were teachers (50.31%), from the School of Pharmaceutical Sciences and Biochemistry; 44.65% (71 persons) contracted the covid-19 disease; 94.37% (67 persons) were treated at home and only 2.82% had to go to the hospital for treatment. 82%, had to resort to the hospital; currently 100% are vaccinated; 100% took medication, highlighting the use of antibacterials with 27.65%; 49.30% of the people who became ill manifested adverse events, within these stand out colic (34.04%) and stomach discomfort (29.79%), being the gastrointestinal system most affected. Conclusions: Approximately half of the community members of a Private university presented adverse drug reactions related to COVID-19 pharmacotherapy, with colic being the main RAM.